Methane production from four forages at three maturity stages in a ruminal in vitro system - Vargas, Juan J.; Pabón, Martha L.; Carulla, Juan E. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Forage characteristics can modify in vitro methane production. There is little information about in vitro methane production of legumes and grasses at different maturity stages in tropical highland grazing systems. Objective: To evaluate the effect of species and forage maturity on in vitro methane production. Methods: Four forage species grown in tropical highlands of Colombia, two grasses: Kikuyu (Cenchrus clandestinus, previously named Pennisetum clandestinum) and ryegrass (Lolium perenne var. Samsum), and two legumes: Lotus (Lotus uliginosus var. Maku) and red clover (Trifolium pratense) were harvested in two paddocks at three maturity stages (young, intermediate, and mature). In vitro 48 h gas production was measured and methane proportion in gas was quantified by gas chromatography. Data were analysed as a randomized complete block (paddocks) design with a factorial arrangement 4×3 (4 species × 3 maturity stages) using the GLM procedure of SAS®. Results: Lotus produced less methane (p<0.01) than ryegrass, clover, and kikuyu (35.5 vs 64.7, 55.7 or 51.4 mL/g degraded organic matter, respectively). Younger forages produced less methane than intermediate and mature forages (42.8 vs 56.3 and 56.4 mL/g degraded organic matter, respectively). Cellulose concentration and organic matter degradability explained 67% (p<0.01) of methane production. Conclusion: Forage composition, presence of condensed tannins, and changes in fermentation patterns may explain the differences observed in in vitro methane production among species and maturity stages.